Timing of post-resistance exercise nutrient ingestion: effects on gastric emptying and glucose and amino acid responses in humans. Issue 9 (17th September 2018) - Kashima, Hideaki; Sugimura, Kana; Taniyawa, Kana; Kondo, Rumi; Endo, Masako Yamaoka; Tanimoto, Shota; Kobayashi, Toshio; Miura, Akira; Fukuba, Yoshiyuki
Abstract: This study examined the effects of post-resistance exercise protein ingestion timing on the rate of gastric emptying (GE) and blood glucose (BG) and plasma branched-chain amino acid (BCAA) responses. In all, eleven healthy participants randomly ingested 400 ml of a nutrient-rich drink containing 12 g carbohydrates and 20 g protein at rest (Con), at 5 min (post-exercise (PE)-5) or at 30 min (PE-30) after a single bout of strenuous resistance exercises. The first and second sets comprised ten repetitions at 50 % of each participant's one-repetition maximum (1RM). The third, fourth and fifth sets comprised ten repetitions at 75 % of 1RM, and the sixth set involved repeated repetitions until exhaustion. Following ingestion of the nutrient-rich drink, we assessed the GE rate using 13 C-sodium acetate breath test and evaluated two parameters according to the T max-calc (time when the recovery per hour is maximised), which is a standard analytical method, and T 1/2 (time when the total cumulative dose of [ 13 CO2 ] reaches one-half). T max-calc and T 1/2 were slower for the PE-5 condition than for either the PE-30 or Con condition ( T max-calc ; Con: 53 (sd 7) min, PE-5: 83 (sd 16) min, PE-30: 62 (sd 9) min, T 1/2 ; Con: 91 (sd 7) min, PE-5: 113 (sd 21) min, PE-30: 91 (sd 11) min, P <0·05). BG and BCAA responses were also slower for the PE-5 condition than for either the PE-30 or Con condition. Ingesting nutrients immediately after strenuous resistance exercise acutely delayed GE, which affected BG and plasma BCAA levels in blood circulation.